PENGARUH KOMITMEN PROFESIONAL,SIKAP DAN PERSEPSI KONTROL TERHADAP WHISTLEBLOWING INTENTION PT. K33 DISTRIBUSI SURAKARTA - Amien Mustofa; Rispantyo Rispantyo; Sunarti Sunarti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
The-purpose of this research are to analyze theesignificance of the effect ofprofessional commitment, attitudes and perceptual control on whistleblowingintentions at PT. K33 Distribution in Surakarta. This research used quantitativemethods with 60 samples from 122 employee at PT. K33 Distribution in Surakartaand measured by the questionnaire method. Sampling using stratifiedrandom0sampling method. Data analysiswwas performed using descriptivestatistical test instruments, classical assumptionntests, multiple linear regressiontests and hypothesisstesting. The results of the analysis from the hypothesis testshow that attitudes have a significant effect onnwhistleblowing intentions, andprofessional commitment and perceptual control have a effect but not significanton whistleblowing intentions.